Preliminary Phytochemical Analysis & Anti-bacterial Activity of Mimosa Pudica Linn Leaves - Rekha Rajendran; R. Sundararajan (International Journal of Pharma and Bio Sciences, 2010)
Mimosa pudica known, as chue Mue, is a prostrate shrubby plant with the compound leaves sensitive to touch, grows as weed in almost all parts of the country. In the present investigation, preliminary phytochemical analysis and antibacterial activity of different extracts (n-hexane, chloroform, ethylacetate, methanol and methanolic fractions (No. I to VIII) of the leaves of Mimosa pudica have been studied. The antibacterial activity was assessed by standard dilution test using Mueller Hinton agar medium. The zone of inhibition of the fraction (VII) was compared with that of Standard antibiotic ciprofloxacin (5mg/disc) by disc diffusion method. The findings showed potential antibacterial properties of the extracts and fractions against the organisms tested. The Minimum inhibitory concentration (MIC) of the extracts and fractions was found to be 133.33 mg/ml. But fraction No.VII was found to have 33.33 mg/ml as MIC against the tested organisms. So the zone of inhibition of that fraction was comparable with that of ciprofloxacin. Preliminary phytochemical analysis may also helps to standardize this plant species from other related species. Our findings confirm that the traditional therapeutic claims for this plant, in near future surely be able to replace the conventional anti-microbial agents to which there is increased incidence of drug interactions and the study suggests that the plant is promising for development of phytomedicine for antibacterial properties.